Gender in mental health: Relationship of spirituality, social support, and COVID-19-related fear among heterosexual and LGBTQ+ youth - Alibudbud, Rowalt (Frontiers in Sociology, 2023)
Introduction The youth is a vulnerable population to COVID-19-related fear. Among them, those with LGBTQ+ identities are at higher risk. Given the posited protective effects of spirituality and social support on fear, this study explored their effects on COVID-19-related fear among heterosexual and LGBTQ+ youth. Materials and methods This cross-sectional study recruited 137 respondents Filipinos aged 18 to 30 years old. The respondents answered a survey containing a sociodemographic questionnaire, 12-items Multidimensional Scale of Perceived Social Support (MSPSS), 20-items Core Dimensions of Spirituality Questionnaire (CDSQ), and 7-items Fear of COVID-19 Scale (FCS). After, the data were analyzed using means, frequencies, Mann-Whitney U-tests, and correlation coefficients. Results Social support from friends was negatively correlated with COVID-19-related fear among heterosexual respondents, R = -.219, p = .029. Search for meaning positively correlated with COVID-19-related fear among LGBTQ+ respondents, R = .395, p = .016. Heterosexual respondents also have a higher belief in God (U = 1004, p <.001) and feelings of security (U = 1110.5, p <.001) than their LGBTQ+ counterparts. Discussion These findings suggest that social support from friends is protective against COVID-19-related fear among heterosexual youth but not among LGBTQ+. A high search for meaning can heighten COVID-19-related fear among LGBTQ+. These findings can be explained by the higher rates of discrimination against LGBTQ+ than heterosexual youth. Thus, gender-responsive mental healthcare is needed to address the youth’s fears as society recovers from the pandemic.